The past, present and future of RNA respiratory viruses: influenza and coronaviruses - Makarov, Vadim (Pathog Dis, 2020)
Influenza virus and coronaviruses continue to cause pandemics across the globe. We now have a greater understanding of their functions. Unfortunately, the number of drugs in our armory to defend us against them is inadequate. This may require us to think about what mechanisms to address. Here, we review the biological properties of these viruses, their genetic evolution and antiviral therapies that can be used or have been attempted. We will describe several classes of drugs such as serine protease inhibitors, heparin, heparan sulfate receptor inhibitors, chelating agents, immunomodulators and many others. We also briefly describe some of the drug repurposing efforts that have taken place in an effort to rapidly identify molecules to treat patients with COVID-19. While we put a heavy emphasis on the past and present efforts, we also provide some thoughts about what we need to do to prepare for respiratory viral threats in the future.